KONSTRUKSI PENDIDIKAN KARAKTER ANAK BERKEBUTUHAN KHUSUS DI TK PELANGI ANAK INDONESIA YOGYAKARTA - Tri Mulat (STAI Sufyan Tsauri Majenang, 2020)
This study aims to determine the level of learning in early childhood education in instilling character education in Pelangi Anak Kindergarten. The type of research used is qualitative with an ethnographic approach. Selection of subjects using purposive sampling, followed by Snow Ball Sampling. Collecting data in this study using the method of observation, interviews and documentation. The success of planting the level of character education can be seen by looking at the results of the assessment that has been carried out by the teacher. The results showed that there were 3 levels of character education in early childhood, namely Top Level Inclusion, Global Link Inclusion, and Character Based Technology.